2017
DOI: 10.3748/wjg.v23.i19.3468
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes recurrence after metabolic surgeries correlates with re-impaired insulin sensitivity rather than beta-cell function

Abstract: AIMTo investigate factors causing diabetes recurrence after sleeve gastrectomy (SG) and duodenal-jejunal bypass (DJB).METHODSSG and DJB were performed on rats with diabetes induced by high-fat diet (HFD) and streptozotocin (STZ). HFD was used to induce diabetes recurrence at 4 wk postoperatively. Body weight, oral glucose tolerance test, homeostatic model assessment of insulin resistance (HOMA-IR), insulin signaling [IR, insulin receptor substrate (IRS)1, IRS2, phosphatidylinositol 3-kinase and AKT in liver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…One possible explanation is that the destruction of substrate IRS1/2 will cause insulin resistance. In addition, many studies have shown that the level of IRS1/2 increases after bariatric surgery [ 35 , 36 ]. These studies provide important insight into the mechanism of PI3K-AKT pathway activation after weight-loss surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the destruction of substrate IRS1/2 will cause insulin resistance. In addition, many studies have shown that the level of IRS1/2 increases after bariatric surgery [ 35 , 36 ]. These studies provide important insight into the mechanism of PI3K-AKT pathway activation after weight-loss surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At present the physiological and molecular mechanisms underlying diabetes remission and relapse after metabolic surgery remains incompletely understood, although in the early stage diabetes remission is mainly due to improvement in insulin sensitivity . Recently Lui Teng based on animal model study found that rapidly improved insulin sensitivity after metabolic surgery relapsed after 8 weeks of high calorie, high‐fat diet (HFD) gavage. They concluded that relapse of hepatic and muscular insulin sensitivity due to HFD is likely responsible for the relapse, not alterations of beta‐cell function and weight regain.…”
Section: Discussionmentioning
confidence: 99%
“…This brings us to the problem of diabetes relapse after SG, which is as high as 41.6% of cases five years after surgery [ 2 ]. Liu et al proposed long-term recovery of insulin sensitivity without beta-cell dysfunction as an answer to the question [ 24 ], but a recent work showed loss of beta-cell mass and a strong increase in alpha-cell mass in Wistar rats twelve weeks after SG. Trans-differentiation of the beta-cell population under stressful situations with loss of beta-cell markers such as PDX-1 and gain of alpha-cell markers such as Pax-6 and Arx has been shown [ 25 ] ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%